Strategic transformation of the business model in the information company - García-Alonso Montoya, Pedro; Shan, Xuesong; Fan, Xiaojing (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Information has become the new fundamental value. It is essential to have updated content, both for companies and entities and for individuals. This is the case in all spheres: cultural and professional, social and economic... If knowledge is power, today’s citizens are the most powerful in all of history because we can learn almost anything we want thanks to the media, via the Internet.But not everything are advantages. New elements have emerged, such as Artificial Intelligence, which can replace professionals. Sadly, the technology that once seemed to be a boon to the press has almost come close to killing it.